Hydryphantoidea Piersig, 1896 (Acari: Parasitengonina: Hydrachnidiae) from South America, with an emphasis in Rhynchohydracaridae: description of new species, homologies of idiosomal structures and a catalog with geographic distribution, a key for species and molecular data - Castro, Luiz Alexandre Simões de [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Ácaros aquáticos, também conhecidos como Hydrachnidia, Hydrachnidiae, Hydrachnellae ou Hydracarina, podem ser encontrados em todos os ambientes de água doce e pertencem à coorte Parasitengonina, caracterizada por um tipo de desenvolvimento único dentro dos Acariformes, em que as larvas ocupam um nicho diferente dos outros estágios: após emergir dos ovos, são hexápodes e procuram um hospedeiro adequado, tornando-se ectoparasitas. O tempo de vida desta fase, assim como o tipo de hospedeiro e os locais de fixação são diversos. Após ingurgitadas, as larvas entram em um estágio quiescente chamado protoninfa, e então passam por uma muda e desenvolvem um quarto par de pernas, atingindo as condições de deutoninfa ativa, tritoninfa inativa e adulto ativo. Por essa razão, adultos e ninfas podem ser encontrados no mesmo ambiente, como predadores. Os Hydrachnidiae são compostos por 7 superfamílias e o monofiletismo deste grupo foi recentemente recuperado por meio de análises moleculares, com exceção de Hydryphantoidea, considerada parafilética. Na América do Sul, esta superfamília é representada por 4 famílias: Hydryphantidae, Hydrodromidae, Rhynchohydracaridae e Thermacaridae. Dentre os Hydryphantoidea, Rhynchohydracaridae apresenta origem sul-americana, com as subfamílias Clathrosperchontinae e Rhynchohydracarinae vivendo em águas correntes límpidas. Nesse contexto, o objetivo deste trabalho foi estudar os Hydryphantoidea da América do Sul com ênfase em Rhynchohydracaridae. Novas espécies dos gêneros Clathrosperchonella (fêmea, macho e larva) e Rhynchohydracarus (fêmea e macho) do Brasil foram descritas. DNA barcodes foram obtidos pela primeira vez para esta família, com sequências do gene COI para Clathrosperchon minor, C. punctatus, Clathrosperchonella olovi sp. nov. e Rhynchohydracarus armiger sp. nov. Uma proposta de homologia para estruturas do idiossoma dorsalia, ventralia, lateralia e glandularia em Rhynchohydracaridae é apresentada, padronizando futuros estudos morfológicos e novas descrições. Novas ocorrências de Hydryphntoidea são relatadas para o Brasil e Equador. Um catálogo de espécies de Hydryphantoidea descritas até o momento para a América do Sul é apresentado, com mapas de distribuição e uma chave ilustrada para famílias, subfamílias, gêneros e subgêneros.

The water mites, also known as Hydrachnidia, Hydrachnidiae, Hydrachnellae or Hydracarina, can be found in all freshwater environments and belong to the cohort Parasitengonina, characterized by a unique type of development within Acariformes, in which the larvae occupy a different niche from the other stages: after emerging from the eggs, hexapod larvae search for a suitable host and become ectoparasites. The life span of this stage, as well as the type of host and the places of attachment, are diverse. After engorged, larvae enter into a quiescent stage called protonymph, and then undergo a molt and develop a fourth pair of legs, reaching the conditions of active deutonymph, inactive tritonymph and active adult. For this reason, adults and nymphs can be found in the same environment, as predators. Hydrachnidiae is composed of 7 superfamilies and the monophyly of this group has been recently recovered by means of molecular analysis, except for Hydryphantoidea, considered paraphyletic. In South America, this superfamily is represented by four families: Hydryphantidae, Hydrodromidae, Rhynchohydracaridae and Thermacaridae. Among hydryphantoids, Rhynchohydracaridae presents a South American origin, with the subfamilies Clathrosperchontinae and Rhynchohydracarinae living in pristine running waters. In this context, the aims of this work were study the Hydryphantoidea of South America with an emphasis in Rhynchohydracaridae. New species of the genera Clathrosperchonella (female, male and larva) and Rhynchohydracarus (female and male) from Brazil are described. DNA barcodes were obtained for the first time for this family, with sequences of the gene COI for Clathrosperchon minor, C. punctatus, Clathrosperchonella olovi sp. nov. and Rhynchohydracarus armiger sp. nov. A proposal for the homologies of dorsalia, ventralia, lateralia and glandularia in Rhynchohydracaridae is presented and should help to facilitate and standardize future morphological studies and descriptions of new species in this family. New reports are presented for Brazil and Ecuador. A catalog of all described species of Hydryphantoidea until the moment for South America is presented, with maps of distribution and an illustrated key for the families, subfamilies, genera and subgenera.
Hydryphantoidea Piersig, 1896 (Acari: Parasitengonina: Hydrachnidiae) from South America, with an emphasis in Rhynchohydracaridae: description of new species, homologies of idiosomal structures and a catalog with geographic distribution, a key for species and molecular data
Keywords: Ácaros aquáticos; Riachos; Morfologia; Taxonomia integrativa; COI; Water mites; Streams; Morphology; Integrative taxonomy